Photophysical Properties and Photobiological Activities of Ruthenium(II) Complexes Bearing π-Expansive Cyclometalating Ligands with Thienyl Groups - McCain, Julia (Inorg Chem, 2019)
A new family of cyclometalated ruthenium(II) complexes [Ru(N^N)(2) (C^N)](+) derived from the π-extended benzo[h]imidazo[4,5-f]quinolone ligand appended with thienyl groups (n=1–4, compounds 1–4) was prepared and characterized for their chemical, photophysical, and photobiological properties. The lipophilicities of 1–4, determined as octanol-water partition coefficients (log P(o/w)), were positive and increased with the number of thienyl units. The absorption and emission bands of the C^N compounds were red-shifted by up to 200 nm relative to the analogous Ru(II) diimine systems. All of the complexes exhibited dual emission, with the intraligand fluorescence ((1)IL, C^N-based) shifting to lower energies with increasing n and the metal-to-ligand charge transfer phosphorescence ((3)MLCT, N^N-based) remaining unchanged. Compounds 1–3 exhibited excited state absorption (ESA) profiles consistent with lowest-lying (3)MLCT states when probed by nanosecond transient absorption (TA) spectroscopy with 532-nm excitation, and had contributions from (1)IL(C^N) states with 355-nm excitation. These assignments were supported by the lifetimes observed (<10 ns for the (1)IL states, and around 20 ns for the (3)MLCT states) as well as a noticeable ESA for 3 with 355-nm excitation that did not occur with 532-nm excitation. Compound 4 was the only member of the family with two (3)MLCT emissive lifetimes (15, 110 ns), and the TA spectra collected with both 355- and 532-nm excitation was assigned to the (3)IL state, which was corroborated by its 4–6 µs lifetime. The ESA for 4 had a rise time of approximately 10 ns and an initial decay of 110 ns, which suggests a possible (3)MLCT-(3)IL excited state equilibrium that results in delayed emission from the (3)MLCT state. Compound 4 was nontoxic toward human skin melanoma cells (SKMEL28) in the dark (EC(50) = >300 µM); 1–3 were cytotoxic and yielded EC(50) values between 1–20 µM. The photocytotoxicites with visible light ranged from 87 nM with a phototherapeutic index (PI) of 13 for 1 to approximately 1 µM (PI = >267) for 4. With red light, EC(50) values varied from 270 nM (PI=21) for 3 to 12 µM for 4 (PI = >25). The larger PIs for 4, especially with visible light, were attributed to the much lower dark cytotoxicity for this compound. Since the dark cytotoxicity contributes substantially to the observed photocytotoxicity for 1–3, it was not possible to assess whether the (3)IL state of 4 led to a much more potent phototoxic mechanism in the absence of dark toxicity. There was no stark contrast in cellular uptake and accumulation by laser scanning confocal and differential interference contrast (DIC) microscopy to explain the large differences in dark toxicities between 1–3 and 4. Nevertheless, the study highlights a new family of Ru(II) C^N complexes where π-conjugation beyond a certain point results in low dark cytotoxicity with high photocytotoxicity, opposing the notion that cyclometalated Ru(II) systems are too toxic to be phototherapeutic agents.